Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/nu12072077
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Patchouli (Pogostemon Cablin Benth.) Essential Oil Improved Metabolic Parameters in Obesity-Induced Sprague Dawley Rats

Abstract: This study investigated effects of patchouli essential oil (PEO) inhalation on metabolic parameters. First, to characterize aromatic compounds in PEO, solid-phase microextraction-gas chromatography/mass spectrometric detection was employed in which 19 aromatic compounds were identified. In GC-olfactometry analysis, linalool, α-patchoulene, and β-patchoulene were found to be the constituents exhibiting the highest similarity to the aromatic compounds in patchouli. In an animal experiment using Sprague Darley ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(46 citation statements)
references
References 39 publications
(66 reference statements)
3
43
0
Order By: Relevance
“…Obesity is a non-communicable disease that can induce complications, and has been recognized as a serious health problem worldwide [1]. Obesity, defined as the state of accumulation of energy and fat in the body, is caused by an increase in energy intake and a decrease in energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity is a non-communicable disease that can induce complications, and has been recognized as a serious health problem worldwide [1]. Obesity, defined as the state of accumulation of energy and fat in the body, is caused by an increase in energy intake and a decrease in energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…Increased body fat can lead to leptin resistance, a status in which the level of leptin increases, while there is no variation in food intake. In addition, this status can increase the prevalence of type 1 and type 2 diabetes, and it can lead to hypertension due to an increase in blood pressure and heart rate beyond the normal status [1,3,4]. Furthermore, excessive accumulation of body fat may induce metabolic syndrome via an increased prevalence of cardiovascular diseases, which may be caused by increased levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-cholesterol), triglyceride (TG), and decreased high-density lipoprotein cholesterol (HDL-cholesterol) [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particular interesting research have been performed with Patchouli EOs (PEO), a plant belonging to the lamiaceae family ( Pogostemon cablin Benth ), that have attracted the interest of many researchers for its anti-inflammatory, antiviral, antioxidant, and wound-repair properties [ 97 , 98 ]. Studies performed on male Sprague Dawley rats kept on a diet of high fat content (HFD) for 12 weeks demonstrated that the inhalation of PEO leads to a reduction in weight and serum leptin levels as well as decreases food intake [ 99 ]. The authors hypothesized that the reduction in leptin is due to a decrease in leptin resistance.…”
Section: Anti-obesity Effect Of Eosmentioning
confidence: 99%
“…The authors hypothesized that the reduction in leptin is due to a decrease in leptin resistance. The main components of PEO are citronellol, a volatile compound that fights obesity by reducing food intake, patchouli alcohol, α-patchoulene, and β-patchoulene, which stimulates the hypothalamus and regulate leptin levels [ 96 , 99 ].…”
Section: Anti-obesity Effect Of Eosmentioning
confidence: 99%